2020
DOI: 10.1038/s41598-020-77058-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved magnetostriction in Galfenol alloys by aligning crystal growth direction along easy magnetization axis

Abstract: Galfenol (Iron-gallium) alloys have attracted significant attention as the promising magnetostrictive materials. However, the as-cast Galfenols exhibit the magnetostriction within the range of 20–60 ppm, far below the requirements of high-resolution functional devices. Here, based on the geometric crystallographic relationship, we propose to utilize the 90°-domain switching to improve the magnetostriction of Galfenols by tuning the crystal growth direction (CGD) along the easy magnetization axis (EMA). Our fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…As is common with milling processes, there is also a consistent reduction in the unit cell parameter with milling time. The initial unmilled lattice parameter of 2.905 Å is in excellent agreement with the literature, , reducing to 2.904 after 27 milling cycles (3.4 h). A consistent reduction in the crystallite size with the milling time is also observed.…”
Section: Resultssupporting
confidence: 89%
“…As is common with milling processes, there is also a consistent reduction in the unit cell parameter with milling time. The initial unmilled lattice parameter of 2.905 Å is in excellent agreement with the literature, , reducing to 2.904 after 27 milling cycles (3.4 h). A consistent reduction in the crystallite size with the milling time is also observed.…”
Section: Resultssupporting
confidence: 89%
“…5(c) that in the phase transition from the L2 1 austenite cubic structure to the 4O martensite orthorhombic structure, the (220) crystal plane is the habitual plane of the parent phase, and a re-stack arrangement is produced on this crystal plane during the phase transformation process. 32,33 Through experiments and calculations, it is found that the alloy will preferentially form the (220) surface during the DS process, which to a certain extent can reduce the energy barrier that needs to be overcome for the martensitic phase transition so that the phase transition is faster and more complete. This, in turn, increases the magnetic entropy change produced by the transition along the (220) direction, effectively improving the magnetocaloric effect of the martensitic phase transition.…”
Section: Resultsmentioning
confidence: 99%
“…These materials represent an example of field-controllable functional polymers in which micron-sized magnetizable particles are embedded into a compliant polymer network, see [ 22 , 23 , 24 ] for a detailed characterization of MAEs. Since the strong coupling of magnetic and mechanical fields allows us to induce mechanical deformations that are significantly larger than magneto-strictive effects observed for single-phase materials [ 25 , 26 , 27 ], MAEs have attracted considerable research interest in the fields of micro-robots [ 28 ] and -pumps [ 29 ], as well as coating materials with variable shapes [ 30 ]. The ability to control their mechanical modulus using an external magnetic field also allows for technical applications in the areas of actuators and sensors [ 31 , 32 , 33 ], vibration absorbers [ 34 ], as well as prosthetic devices with tunable stiffness [ 35 ].…”
Section: Introductionmentioning
confidence: 99%